The Pterophoridae fauna of Mali (Insecta: Lepidoptera) - Petr Ya. Ustjuzhanin; Vasily N. Kovtunovich; Alexey M. Prozorov; Mohamed M. Traore; Günter C. Müller (SHILAP, 2024)
Nine species of Pterophoridae are recorded for the Republic of Mali. All species except Exelastis pumilio (Zeller, 1873) are recorded for the fauna of the country for the first time.